Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1034/j.1601-0825.2002.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance and management of periodontal lesions in HIV infection

Abstract: Research of the effectiveness of interventions for HIV-associated periodontal lesions is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 38 publications
0
35
0
1
Order By: Relevance
“…Treatment of periodontal diseases in HIV-infected patients has been reviewed by Robinson et al [41,43]. Standard treatments, maintenance and prevention have been shown to be effective.…”
Section: Necrotizing Ulcerative Periodontitis (Nup; Formally Hiv-assomentioning
confidence: 98%
“…Treatment of periodontal diseases in HIV-infected patients has been reviewed by Robinson et al [41,43]. Standard treatments, maintenance and prevention have been shown to be effective.…”
Section: Necrotizing Ulcerative Periodontitis (Nup; Formally Hiv-assomentioning
confidence: 98%
“…This considerable variation can be due to lack of clear diagnosis standardization and the heterogeneity of the population's studies. The existence of Linear Erythematous Gingivitis as a periodontal disease entity that is strongly associated with HIV has been questioned by someand others suggested that Linear Erythematous Gingivitis is mostly misdiagnosed as gingivitis 11,12,13 .…”
Section: Linear Erythematous Gingivitismentioning
confidence: 99%
“…They belong among the earliest clinical features of the infection and could predict progression of HIV disease to AIDS. (Robinson et al, 2002;Coogan et al, 2005). It should also be mentioned that for patients on antiretroviral therapy, HIV-related oral lesions in general, may suggest possible treatment failure as will be further discussed in the present review.…”
Section: )mentioning
confidence: 99%
“…HIV infection in adults is linked with the expression of various types of periodontal lesions, which include specific forms of gingivitis and necrotizing periodontal diseases, as well as with possible exacerbation of preexisting periodontal disease Robinson et al, 2002;EC-Clearinghouse, 1993 …”
Section: Features Of Periodontal Lesions In Hiv Infected Patientsmentioning
confidence: 99%